2012
DOI: 10.1016/j.virol.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional and immunochemical cross-reactivity of V2-specific monoclonal antibodies from HIV-1-infected individuals

Abstract: The recent analysis of the first successful RV144 vaccine trial revealed that a high titer of plasma anti-V2 antibodies (Abs) correlated with a decreased risk of HIV-1 infection in vaccine recipients. To understand the mechanism of immune correlates, we studied seven anti-V2 monoclonal Abs (mAbs) developed from HIV-1 infected individuals. The V2 mAbs target conserved epitopes, including the binding site for α4β7 integrin, and are broadly cross-reactive with various gp120 proteins. Preferential usage of the VH1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
145
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(154 citation statements)
references
References 62 publications
8
145
0
1
Order By: Relevance
“…These Abs do not exhibit unusual structural or genetic characteristics, and their immunoglobulin genes undergo relatively little somatic hypermutation from germline (17,18). Conventional Abs have long been known to protect against infection in animal systems.…”
Section: Types Of Antibodies Conventional Absmentioning
confidence: 99%
See 1 more Smart Citation
“…These Abs do not exhibit unusual structural or genetic characteristics, and their immunoglobulin genes undergo relatively little somatic hypermutation from germline (17,18). Conventional Abs have long been known to protect against infection in animal systems.…”
Section: Types Of Antibodies Conventional Absmentioning
confidence: 99%
“…The structure of this region has so far not been solved, suggesting that it is highly flexible and dynamic. Abs targeting V2i are highly cross-reactive in binding to monomeric gp120 but do not neutralize HIV well (18), suggesting that the epitope is mostly occluded from Ab recognition in the trimeric envelope. V2p epitope.…”
Section: Abs Targeting Variable Loops 1 and 2 (V1v2)mentioning
confidence: 99%
“…Their epitopes are also located in strand B, overlapping the V2q epitope region, but have a helical or helical-coil structure, different from the beta strand structure of the V2q type (22). The V2i type is defined by a panel of seven human MAbs, including 830A, 697-30D, and 2158 (17,23). Extensive immunological, mutagenesis, and computational modeling data have shown that the V2i epitopes overlap the integrin-binding site and likely recognize discontinuous regions in V1V2 (17,18,23).…”
mentioning
confidence: 99%
“…The V2i type is defined by a panel of seven human MAbs, including 830A, 697-30D, and 2158 (17,23). Extensive immunological, mutagenesis, and computational modeling data have shown that the V2i epitopes overlap the integrin-binding site and likely recognize discontinuous regions in V1V2 (17,18,23). However, the precise nature of the V2i epitopes is still unknown.…”
mentioning
confidence: 99%
“…15 We tested the possibility that the rescued IgG1s recognize the heterodimer in its native membrane-bound form by using 293T cells transfected with constructs encoding full E1E2 polypeptides. 12 We specifically selected E1E2 of the HCV genotypes 1b and 2a matching the infected patients genotypes, as well as E1E2 derived from the HCV isolate H77 of genotype 1a.…”
Section: Resultsmentioning
confidence: 99%